Social norms, social behaviours and health: an empirical examination of a model of social capital - Peter Smith; Michael Polanyi (Elsevier, 2003)
Abstract Objective:To explore a model of social capital, specifically the association between socially oriented norms and behaviours and the effect that these factors have on the gradient between income and self‐rated health across three different welfare states. Method:We used data from the 1995-97 World Values Survey, a cross‐sectional study conducted in a variety of countries including Australia, United States, Sweden and Norway (n=5,096). Results:We found variation in the level of social capital measures across the three different welfare states. Socially oriented norms are not strongly correlated with each other, or with socially oriented behaviours. The presence of socially oriented nor ms or behaviours did not reduce the likelihood of lower income groups reporting poor self‐rated health, relative to the highest income groups. Conclusions and implications:Many questions still exist regarding the relationship between social capital and health, including how to measure the social capital concept and whether and how social capital affects health, independent of material and economic conditions.